THE MULTIVARIATE STATISTICAL ANALYSIS OF ABIOTIC PARAMETERS OF THE LAKE TANGANYIKA SUB CATCHMENT - Nkotagu, H. H. (Tanzania Journal of Engineering and Technology, 2018)
Results from multivariate statistical analysis of abiotic parameters conducted during the dry season at 20 accessible sites on 8 rivers, 2 lakes and a dam covering the Lake Tanganyika sub catchment are discussed. Standard methods were used to determine the levels of abiotic parameters from water samples. Physical parameters including DO, EC, Eh, turbidity, temperature, pH and secchi transparency were measured in situ while chlorophyll a was determined in the laboratory. Nutrients such as NO 3- , SiO 2 , PO 43- and Fe 2+ were determined along with HCO 3- . Factor analysis resulted in four factors including increased primary productivity, redox conditions, dissolution, and reduction processes. Processes including dissolution, diffusion, adsorption, absorption, nitrification, denitrification, mixing and reduction along with the anthropogenic activities, increased photosynthetic activity of algae and the geomorphology of the ecosystems contribute to the variation of the abiotic parameters. It is recommended that quantification of river flows, sediment load and nutrient budget at various sampling points be determined seasonally for proper evaluation of the hydrologic and limnological functioning of the ecosystem.